School psychology and social justice : conceptual foundations and tools for practice - Shriberg, David (New York : Routledge, 2013)
"This book will provide an introduction to social justice from the perspective of the major topics that affect school psychology practice"--
pt. 1. Foundations -- pt. 2. Major issues that affect practice -- pt. 3. Roles and functions of school psychologists.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: School psychology -- United States; Social justice -- United States; Education -- Social aspects -- United States; Educational sociology -- United States; Electronic books